THE LECTURERS’ AND STUDENTS’ RESPONSE ON INDEPENDENT LEARNING-INDEPENDENT CAMPUS (MBKM) IN TEACHING AND LEARNING ENGLISH - Sukmawati Sukmawati; Nur Ina Syam; Muliaty Ibrahim; Nurul Amaliah; Sujarwo Sujarwo (Jurnal Scientia, 2023)
This study aimed to analyze the lecturers’ and students’ response on independent learning - independent campus (MBKM) in teaching and learning English. This study used a qualitative approach with descriptive analysis to examine the opinions of lecturers and students. The research sample was only 7 lecturers and 12 students who had passed in independent learning - independent campus program. Data was collected through surveys in the form of response questionnaires distributed to lecturers and students who have joined the program which purpose was to measure the success of MBKM activity process. The results show that there was a good understanding of students, several lecturers regarding policies of MBKM Program that have been chosen by the students namely student exchange, teaching assistant in an educational unit and build villages/thematic community service program have good response for the students. It can be concluded that MBKM program properly implemented, graduates with both hard and soft skills (speaking, writing and reading) who are prepared to face the world of work on their own, creatively, and toughly especially teaching and learning English